Pengaruh Variasi Latihan Smash Bola Gantung Terhadap Ketepatan Smash Bola Voli Pada Atlet Remaja Putri Klub Poncogati Kabupaten Blitar - Elvins Pratiwi Agustin Dwi Putrianti; Supriyadi Supriyadi; Verlina Maya Gita (Universitas Palangka Raya, 2024)
Volleyball is a fun and easy game to play together in a team. In the game of volleyball, players must understand four basic techniques: serve, passing, block, and smash. A very important basic technique in earning or scoring points is smash. This study aims to determine the effect of smash training using hanging balls on smash accuracy in female athletes at the Poncogati Club, Blitar Regency. The method used in this study is a quantitative method of experimentation with One Group Pretest-Posttest Design research design. The population and sample in this study were 21 junior high school students using the purposive sampling method, which means the entire population is taken randomly according to certain criteria. The data analysis techniques applied are descriptive analysis tests, hypothesis tests, and normality tests. The results of this study showed that the Sig.(2-tailed) value of 0.00 in the T test could be concluded that there was a significant influence between the variation of smash training using hanging balls on the accuracy of smashes in young female volleyball athletes of the Poncogati club.